The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2147/ppa.s275887
|View full text |Cite
|
Sign up to set email alerts
|

<p>Perceived Self-Efficacy and Associated Factors Among Adult Patients with Type 2 Diabetes Mellitus at Public Hospitals of Western Ethiopia, 2020</p>

Abstract: Background: Diabetes Mellitus is a chronic disease and can be self-managed using five treatment approaches, including education, medical nutrition therapy, physical exercise, pharmacological intervention, and blood sugar monitoring. Improvement of patient compliance and self-efficacy are critical points that impact the self-care behavior in patients with type two diabetes mellitus in order to limit the morbidity and promote glycemic control. Therefore, the present study successfully assesses the effect of perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
(27 reference statements)
1
17
0
Order By: Relevance
“…Suksatan 22 also found that the perceived benefits of adopting HPBs influenced the HPBs of people at risk of hypertension in a rural Thai community (β = 0.402; p < 0.001). Additionally, perceived self-efficacy is a significant factor influencing HPBs and can predict the health outcomes of hospitalization and the quality of life of patients with NCDs (eg, diabetes, 32 hypertension, 33 heart failure, 34 and COPD 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Suksatan 22 also found that the perceived benefits of adopting HPBs influenced the HPBs of people at risk of hypertension in a rural Thai community (β = 0.402; p < 0.001). Additionally, perceived self-efficacy is a significant factor influencing HPBs and can predict the health outcomes of hospitalization and the quality of life of patients with NCDs (eg, diabetes, 32 hypertension, 33 heart failure, 34 and COPD 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…This result coincided with findings reported by Oluma et al and Xie et al who observed the positive impact of living with a partner on improved adherence outcomes. 10 , 14 We reiterate the critical role of personal and social support; patient adherence is often conditional on external influences, dyadic adjustment being one key aspect. While exploring the dynamics between the patient and her partner (if any) is not part of the routine clinical assessment, our results support that complications in the personal relationship can move high adherence patients to become middle or low adherers.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 7 , 9 Oluma et al also confirmed that keeping a long-term special diet was strongly associated with increased self-efficacy beliefs. 10 Most importantly, higher levels of HbA1c were linked to the number of occasions eating out (i.e., social eating), situations in which strong dietary self-efficacy should guard patients against not exercising nutritional control. 11 Besides eating self-efficacy, improved weight management self-efficacy was also observed to advance glycemic control and keep food regulation in balance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-efficacy refers to the belief of individuals that they have the technical, psychological and knowledge capacity to conduct the essential actions for the implementation of their therapies. In the case of diabetes, it is closely related to glycemic management (4) .…”
Section: Introductionmentioning
confidence: 99%